Crude Ethanol Extract of Diospyros mespiliformis Hochst. ex A. DC. Ebenaceae Leaf and Its Fractions Ameliorate Hyperglycemia and Hyperlipidemia in Alloxan-induced Diabetic Rats - Dahiru, Mubarak Muhammad; Musa, Neksumi (Journal of Tropical Pharmacy and Chemistry, 2024)
This study investigated the antidiabetic activity of the crude ethanol extract of Diospyros mespiliformis (DM) and its ethyl acetate (EEF) and aqueous (AQF) fractions on alloxan-induced diabetic rats. The result indicated a significant (p < 0.05) decrease and improvement in fasting blood glucose (FBG) level and body weight, respectively. The treatment groups exhibited a significantly (p < 0.05) decreased aspartate aminotransferase (AST) level (100-117 IU/L) and decreased gamma-glutamyl transferase (GGT) level in the EEF (4.80 ± 1.02 IU/L) and AQF (5.80 ± 0.80 IU/L) groups only. All the extract-treated groups exhibited a significant increase (p < 0.05) in urea and creatinine levels than the naïve control group (6.94 ± 0.20 mM/L). Moreover, the Na+ remained significantly (p > 0.05) unchanged while the K+ level was significantly (p < 0.05) increased for the treatment groups. The HCO3- of the treated groups increased significantly (p < 0.05) except for the AQF (21.60 ± 1.63 mM/L) group. The total cholesterol and triglyceride levels decreased significantly (p < 0.05) for the treatment groups while the high-density lipoprotein-cholesterol (HDL-C) and low-density lipoprotein-cholesterol (LDL-C) levels remained unchanged but significantly higher than the metformin group. DM possesses significant hypoglycemic and hypolipidemic activity lowering hyperglycemia and hyperlipidemia, and improving body weight and diabetic markers.